Native o foreing strains of trichoderma for control of rhizoctoniasis in yellow potato - Hoyos C, Lilliana; Galvis, Felipe; Rodríguez, David (Revista de Ciencias Agrícolas, 2012)
The aim of this study was the search and analysis of isolates of Trichoderma spp. with biocon- trol potential against R. solani causing rhizoctoniasis in potato (S. tuberosum group phureja). Were obtained 55 strains of Trichoderma from rhizosphere and soil in potato crops, grasses and peas in Cundinamarca and Boyacá, and other from warmer areas (Cundinamarca and Cesar), in order to contrast the effectiveness of strains from potato agroecosystem and others from of different soils and agroecological zones. Of these, 5 strains were selected and was used also a commercial product. T07 and T51, from P. edulis and S.tuberosum showed signi- ficant proportion of healthy stems and fewer sclerotia; treatments with strains T07, T48 and T51 showed significant differences results for the variables of health and physiology of the plant (root number, diameter and health) assessed during this trial, being more efficient in the process of adaptation and colonization of substrate; also those strains present tolerance at validamycin, used for chemical control of R. solani. In contrast to Trichoderma T41 from S. tuberosum, do not protect tubers and do not reveal tolerance to the fungicide. Finally can be concluded that is possible to use native and foreign strains, because the source of the antagonist is not a determinant of biological activity (mycoparasitism), adaptation to soil or management conditions (fungicide tolerance), because antagonistic behavior depends more on the characteristics metabolic isolation of Trichoderma and its interaction with the patho- gens and the plant.